Single-cell sequencing-based study of ferroptosis mechanisms in heat stroke: identification of key biomarkers and dynamic analysis of the immune microenvironment - Defeng Yin; Qin Guo; Hao Jiang; Yonglan Hu; Lu Liu; Xiang Li; Chenglin Wang; Shilin Li; Kaiyu Jin; Yingchun Hu (BMC Medical Genomics)
Abstract Background Heat stroke, caused by excessive heat production or impaired dissipation, often results from prolonged heat exposure or strenuous activity. Ferroptosis, a novel form of programmed cell death, has been implicated in its pathogenesis, though its mechanisms remain unclear. Objective This study investigates the molecular mechanisms linking heat stroke and ferroptosis using single-cell and transcriptomic analyses to identify diagnostic and therapeutic targets. Methods Peripheral blood samples from 29 heat stroke patients, recruited at an early stage of the condition, underwent transcriptome sequencing, and single-cell RNA sequencing was conducted for two representative cases. Ferroptosis-related genes were identified by integrating the FerrDB database, followed by weighted gene co-expression network analysis (WGCNA) and differential gene expression analysis to pinpoint ferroptosis-related genes most characteristic of heat stroke. Functional enrichment analyses, including GO and KEGG pathways, were performed. Single-cell RNA sequencing revealed immune microenvironment alterations and marker genes linked to heat stroke pathogenesis. Receiver operating characteristic (ROC) analysis evaluated the diagnostic potential of these genes. Additionally, pseudotime analysis elucidated cell differentiation trajectories and the roles of key genes. Results In Dataset 1, 630 differentially expressed genes (546 up-regulated, 84 down-regulated) and 1,979 heat stroke-related genes were identified. Among them, 14 intersected with 1,001 ferroptosis-related genes and were enriched in pathways like fatty acid metabolism, inflammation, and immune regulation. Single-cell sequencing showed increased monocytes and macrophages in heat stroke patients. Five core genes (ACSL1, MAPK14, ALOX5AP, PROK2, and DUSP1) were validated in Dataset 2 with high AUC values (1.0, 1.0, 0.952, 0.976, and 0.881, respectively). These genes were highly expressed in neutrophils, dendritic cells, and monocytes. Pseudotime analysis confirmed their roles in cell differentiation and disease progression. Conclusion ACSL1, MAPK14, ALOX5AP, PROK2, and DUSP1 were identified as novel biomarkers for diagnosing heat stroke. ROC validation confirmed their strong association with the disease, highlighting their potential as diagnostic targets. Pseudotime analysis revealed their consistency in cellular differentiation trajectories.